2017
DOI: 10.4103/meajo.meajo_232_16
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and glaucoma surgery: Endoscopic cyclophotocoagulation versus trabeculectomy

Abstract: PURPOSE:To compare the efficacy and safety of endoscopic cyclophotocoagulation (ECP) versus trabeculectomy with mitomycin C (trab) in combination with cataract surgery.MATERIALS AND METHODS:We evaluated the 6-month results of patients undergoing phacoemulsification (phaco) with either ECP or trab. The primary outcome was mean intraocular pressure (IOP) at 6 months; secondary outcomes were change in glaucoma medications, visual acuity, intraocular inflammation, and postoperative complications. Complete success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Ten of the included studies[ 30 31 33 34 35 36 37 38 39 ] reported the success rate of ECP and non-ECP in treating refractory glaucoma. These values were reported based on the longest follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the included studies[ 30 31 33 34 35 36 37 38 39 ] reported the success rate of ECP and non-ECP in treating refractory glaucoma. These values were reported based on the longest follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Another prospective study published earlier also concluded that phaco-ECP was an effective alternative to phaco-trabeculectomy in reducing IOP and medication requirement, and was reasonably safe with a similar rate of additional surgical intervention (43). Compared to trabeculectomy alone, ECP is generally associated with less serious complications except in refractory glaucoma (44), and the most common complications are IOP spikes (14.5%) and hemorrhages (3.8%) according to the ECP Collaborative Study (45). Performing ECP with phacoemulsification has not been shown to increase the risk of serious complications compared to phacoemulsification alone (42).…”
Section: Endoscopic Cyclophotocoagulation (Ecp)mentioning
confidence: 98%
“…5 Trabeculectomy, the standard therapy for glaucoma, has a beneficial effect of lowering intraocular pressure. 6,7 However, clinical practice has revealed that in the course of treatment, patients' filters are susceptible to tissue edema, 8 fibroplasia and wound repair, which may result in blockage of filters, interruption of drainage, and ultimately operation failure. Moreover, the incidence of operationrelated complications may be high, resulting in poor therapeutic outcomes.…”
Section: Original Articlementioning
confidence: 99%